2019
DOI: 10.1002/tee.22936
|View full text |Cite
|
Sign up to set email alerts
|

Vehicle‐localization‐based and DSRC‐based autonomous vehicle rear‐end collision avoidance concerning measurement uncertainties

Abstract: Rear‐end collision is one of the most serious accidents for vehicles, some rear end collision avoidance systems have been developed to protect vehicles from rear‐end collisions. Current rear‐end collision avoidance systems mainly utilize vehicle‐relative measurement sensors to acquire information on surrounding vehicles, considering limited detection ranges and impaired performance in bad weathers of these vehicle sensors, currently used collision avoidance systems cannot guarantee vehicle safety in all enviro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Ref. [94] proposed a modern Dedicated-Short-Range-Communication (DSRC) intervehicle communication system along with vehicle localization-based rear-end collision avoidance methods, to help the AVs avoid rear-end collisions. Hongliang Yuan et al [147] suggested a decision-making strategy for autonomous driving to avoid traffic collisions.…”
Section: Collision Avoidancementioning
confidence: 99%
“…Ref. [94] proposed a modern Dedicated-Short-Range-Communication (DSRC) intervehicle communication system along with vehicle localization-based rear-end collision avoidance methods, to help the AVs avoid rear-end collisions. Hongliang Yuan et al [147] suggested a decision-making strategy for autonomous driving to avoid traffic collisions.…”
Section: Collision Avoidancementioning
confidence: 99%
“…In reference [81], DSRC is applied to communicate with surrounding vehicles, and the real-time state of vehicles determined by the vehicle dynamics model and braking system dynamics, which prevents rear-end collision with other vehicles and illustrates the reliability of DSRC communication. However, AD requires safety redundancy in the event of communication interference, and integration with other sensors is essential.…”
Section: E Vehicular Communicationsmentioning
confidence: 99%
“…Moreover, DS is effective in managing uncertainty in multisensor environments [15]. We begin by summarizing the mathematical framework of DS [16,19,20,40,41].…”
Section: Dempster-shafer Theory Of Evidencementioning
confidence: 99%
“…This problem is due to combining in (3) which ignores the conflicts in evidence. In order to illustrate this problem, let us consider the following example [19,40,43]. Given 3 events Z = {A, B, C} and 2 Observers, Observer 1 and 2 assign m 1 (A) = 0.9, m 1 (B) = 0.1, m 1 (C) = 0.0 and m 2 (A) = 0.0, m 2 (B) = 0.1, m 2 (C) = 0.9 as confidences in Z, respectively.…”
Section: Data Fusion For the Existence Of Objectsmentioning
confidence: 99%